Analisis Disiplin , Budaya Kerja dan Motivasi Terhadap Produktivitas Kerja Karyawan di PT. Adi Satria Abadi Bantul (Discipline Analysis, Work Culture and Motivation on Work Productivity of Employees in PT. Adi Satria Abadi Bantul) - Jalal Firdaus; Kusuma Chandra Kirana; Prayekti Prayekti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
The purpose of this study was to describe (1) The Effect of Discipline on Employee Productivity at PT. Adi Satria Abadi Bantul. (2) Effect of Work Culture on Employee Productivity at PT. Adi Satria Abadi Bantul. (3) The Effect of Motivation on Employee Product Productivity at PT. Adi Satria Abadi Bantul. (4) Effect of Discipline, Work Culture, and Motivation on Employee Productivity at PT. Adi Satria Abadi Bantul.The research population is employees of PT. Adi Satria Abadi Bantul, amounting to 300 employees. The sample of this study was taken by 60 employees by using accidental sampling technique, a technique that does not provide the same opportunity / opportunity for each member of the population to be selected as sample members. Data analysis used is multiple linear regression to identify independent variables that affect the dependent variable.The results show that (1) Discipline does not have a significant positive effect on Employee Productivity (2) Work culture has a significant positive effect on Employee Productivity. (3) Motivation has a significant positive effect on Employee Productivity. (4) Discipline, Work Culture, and Motivation have a significant positive effect on Employee Productivity.